Automatic Bus Fare Collection System using RFID - Ban, Missan; Singh, Nabin; Lamichhane, Ronash; Ban, Samir; Shrestha, Ajaya; Pokhrel, Anisha (Journal of Advanced College of Engineering and Management, 2025)
Public transportation systems in developing regions often depend on manual fare collection methods that are inefficient, more prone to human error and vulnerable to fare evasion and revenue leakage. This research implements an Automatic Bus Fare Collection System which uses Radio Frequency Identification (RFID) and Global Positioning System (GPS) technologies to manage these challenges. The objective of this system is to automate fare collection based on real-time passenger tracking and distance traveled, helping in improving passenger experience. The system is built with an ESP32 microcontroller at the center, RFID readers installed at bus entry and exit points and a GPS NEO-6M module for real-time location tracking. A database records details of fare transaction, whereas a web-based interface enables users to manage accounts and view payment history. Integration with the eSewa digital payment gateway facilitates remote balance recharge. The system experimental testing confirmed accurate fare calculation, reduced boarding time, and minimized dependency on conductors. The system also improves security through encrypted communication and user authentication. Identified challenges include misplacement of the RFID card, initial infrastructure costs, and the need to adapt to the user. Despite these, the system shows strong potential as a reliable, scalable and cost-effective alternative to traditional fare collection systems. It sets a practical foundation for the adoption of intelligent transport infrastructure in urban environments, particularly in the context of developing nations.